2016
DOI: 10.1177/0340035216672238
|View full text |Cite
|
Sign up to set email alerts
|

Data governance, data literacy and the management of data quality

Abstract: Data governance and data literacy are two important building blocks in the knowledge base of information professionals, involved in supporting dataintensive research, and both address data quality and research data management. Applying data governance to research data management processes and data literacy education helps in delineating decision domains and defining accountability for decision making. Adopting data governance is advantageous, because it is a service based on standardised, repeatable processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 38 publications
1
72
0
1
Order By: Relevance
“…Which type of governance should serve as the foundation of data governance for higher education and how it should it vary based on the institutional view on data and information? As Koltay (2016) suggested, "librarianship as well as library and information science also should pay attention to DG [data governance], albeit it attracted attention mainly in the business sector" (p. 304). It is our attempt to examine data governance in higher education from an information science perspective in hopes of understanding the significance of the interplay of data governance, IT governance, and information governance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Which type of governance should serve as the foundation of data governance for higher education and how it should it vary based on the institutional view on data and information? As Koltay (2016) suggested, "librarianship as well as library and information science also should pay attention to DG [data governance], albeit it attracted attention mainly in the business sector" (p. 304). It is our attempt to examine data governance in higher education from an information science perspective in hopes of understanding the significance of the interplay of data governance, IT governance, and information governance.…”
Section: Discussionmentioning
confidence: 99%
“…In order to collect relevant data that are meaningful for analysis, a Data Governance Checklist was developed. It is derived from key literature on data governance with seven major criteria identified that would fit for the context of higher education (Brous, et al, 2016;Khatri & Brown, 2010;Koltay, 2016;Li, et al, 2016;Otto, 2011). A coding schema was developed to examine and collect evidence of the status quo of their data governance practices.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations